1993
DOI: 10.1143/jjap.32.5312
|View full text |Cite
|
Sign up to set email alerts
|

High Density Magneto-Optical Recording with a Second-Harmonic Generation Green Laser

Abstract: Tripled areal density optical recording was realized with the combination of a high power laser-diode pumped intracavity frequency-doubled Nd:YAG laser (SHG green laser), a low noise GdFeCo/TbFeCo double-layered magneto-optical (MO) disk, and high sensitivity photodetectors optimized for the wavelength of the light source. A high carrier-to-noise (C/N) ratio of more than 48 dB and a bit error rate of less than 3×10-6 by (2, 7) run-length-limited (RLL) mark position recording was obtained at a mark length of 0.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1995
1995
1997
1997

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(1 citation statement)
references
References 8 publications
0
1
0
Order By: Relevance
“…Recently, a comparably increased information storage capacity of the magnetic recording media due to persistent research and development motivated the use of short wavelength lasers for writing and reading in the magneto-optical media. [2][3][4] However, the readout carrier-to-noise ratio ͑CNR͒ is known to decrease due to a deteriorated Kerr rotation angle at the short wavelengths. It has been reported that the static magnetic properties of Tb-Fe-Co thin films are influenced to a large extent by the sputtering parameters of the magneto-optical layer.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, a comparably increased information storage capacity of the magnetic recording media due to persistent research and development motivated the use of short wavelength lasers for writing and reading in the magneto-optical media. [2][3][4] However, the readout carrier-to-noise ratio ͑CNR͒ is known to decrease due to a deteriorated Kerr rotation angle at the short wavelengths. It has been reported that the static magnetic properties of Tb-Fe-Co thin films are influenced to a large extent by the sputtering parameters of the magneto-optical layer.…”
Section: Introductionmentioning
confidence: 99%